Production, recovery and purification of a recombinant β-galactosidase by expanded bed anion exchange adsorption - Boeris, Valeria (2012)
β-Galactosidase is a hydrolase enzyme that catalyzes the hydrolysis of β-galactosides into monosaccharides; its major application in the food industry is to reduce the content of lactose in lactic products. The aim of this work is to recover this enzyme from a cell lysate by adsorption onto Streamline-DEAE in an expanded bed, avoiding, as much as possible, biomass deposition onto the adsorbent matrix. So as to achieve less cell debris-matrix interaction, the adsorbent surface was covered with polyvinyl pyrrolidone. The enzyme showed to bind in the same extent to naked and covered Streamline-DEAE (65. mg β-gal/g matrix) in batch mode in the absence of any biomass. The kinetics of the adsorption process was studied and no effect of the polyvinyl pyrrolidone covering was found. The optimal conditions for the recovery were achieved by using a lysate made of 40% wet weight of cells, a polyvinyl pyrrolidone-covered matrix/lysate ratio of 10% and carrying out the adsorption process in expanded bed with recirculation over 2. h in 20. mM phosphate buffer pH 7.4. The fraction recovered after the elution contained 65% of the initial amount of enzyme with a 12.6-fold increased specific activity with respect to the lysate. The polyvinyl pyrrolidone content in the eluate was determined and found negligible. The remarkable point of this work is that it was possible to partially purify the enzyme using a feedstock containing an unusually high biomass concentration in the presence of polyvinyl pyrrolidone onto weak anion exchangers.